Depleted cultural richness of an avian vocal mimic in fragmented habitat. (30th October 2022) - Backhouse, Fiona; Welbergen, Justin A.; Magrath, Robert D.; Dalziell, Anastasia H.
Abstract: Aim: Conservation has recently shifted to include behavioural or cultural diversity, adding substantial value to conservation efforts. Habitat loss and fragmentation can deplete diversity in learnt behaviours such as bird song by reducing the availability of song tutors, yet these impacts are poorly understood. Vocal mimicry may be particularly sensitive to habitat loss and fragmentation through the resulting reduction in both heterospecific models and conspecific tutors. Here we examine the relationship between habitat availability and both mimetic repertoire size and song composition in male Albert's lyrebirds ( Menura alberti ), a near‐threatened species renowned for its remarkable mimetic abilities. Location: Eastern Australia. Methods: We calculated repertoire size and composition from recordings of male Albert's lyrebirds from throughout the species' range. We estimated patch size and local habitat availability using a species distribution model and remotely sensed vegetation types. We assessed the local model species assemblage through species distribution models and automated acoustic detectors. Results: Individual males in smaller habitat patches, or in areas with a lower proportion of suitable habitat, mimicked fewer model species and fewer vocalization types. However, they mimicked comparatively more vocalizations from each model species than individuals in larger patches or with more intact habitats. All model species were likely to occur in most study sites, suggesting that repertoires are not driven by the availability of model species. Main Conclusions: Our results suggest that mimetic repertoire sizes are influenced by habitat availability through the number of lyrebird tutors. Further, individuals in disturbed habitats may partially compensate for mimicking fewer species by mimicking more vocalizations from each species. This study supports the hypothesis that cultural diversity may be impoverished by habitat loss and fragmentation in a similar way to genetic diversity. Variation in song diversity may therefore indicate population health and highlight populations in particular need of conservation action.